Analytical geochemistry in the service of medicine: An experimental study of urinary stones from Northern Greece - Iordanidis, A.; Garcia-Guinea, J. (Bulletin of the Geological Society of Greece, 2013)
Knowledge of the precise human biomineral composition may allow physicians to recommend an appropriate prophylactic therapy for the patient and thus prevent or delay the stone recurrence. The present study focuses on the application of complementary analytical techniques to the characterization of human urinary stones. Several gallbladder and renal stone samples were obtained from patients dwelling in areas of northern Greece. A comprehensive analytical study took place, employing the following, common in analytical geochemistry, techniques: Environmental Scanning Electron Microscopy (ESEM) coupled to Energy Dispersive System (EDS), X-Ray Diffraction (XRD), thermogravimetry (TG), μRaman spectroscopy and Cathodoluminescence (CL). A detailed determination of morphological, micro-structural, molecular, chemical and mineralogical characteristics of the urinary stone samples was achieved. It was evident by our study the application of powerful analytical techniques could substantially help the medical advisors to ascribe a medical treatment of diseases related to stone formation.